Structure, reactivity, luminescence and magnetism of dinuclear Ln 3+ complexes produced by the Ln3+-assisted hydrolysis of 3,6-bis(2-pyridyl)tetrazine - Panayiotidou, Lefkia; Drouza, Chryssoula; Arabatzis, Nikos B.; Lianos, Panagiotis; Stathatos, Elias; Viskadourakis, Zacharias; Giapintzakis, John; Keramidas, Anastasios D. (My University, 2013)
Twelve Pr3+, Sm3+, Eu3+, Gd3+, Tb3+ and Dy3+ complexes of N-(pyridin-2-ylmethylene) picolinohydrazonate (phzp-) were synthesized by the Ln3+ assisted hydrolysis of 3,6-bis(2-pyridyl)-1,2,4,5-tetrazine. Crystallographic characterization of Pr3+, Sm3+ and Eu3+ hydrazonate complexes with nitrate or trifluoroacetyleacetonate co-ligands shows them to have binuclear structures with a planar Ln2O2 core and the ligand to be in its mono-anionic form. Exception is the Pr 3+ complex with nitrate co-ligand, which is a mononuclear species containing the neutral hydrazone. Paramagnetic 1D 1H and 2D gCOSY and gNOESY-gEXSY 1H NMR spectroscopies revealed the presence of different isomers exhibiting a sterically controlled fluxional behavior. In addition, phzp- significantly enhances the luminescence of Eu 3+ and Tb3+. Magnetic measurements show antiferromagnetic coupling between the Ln3+ ions in the dinuclear complexes. The structural characterization of the complexes in both solid state and solution show the versatility of phzp- ligand to adopt various ligating motifs.
Keywords: Praseodymium; Samarium; Europium; Gadolinium; Terbium; Dysprosium; Acylhydrazone; Crystal structure; Reactivity; Luminescence; Magnetism